(untitled) (Veterinária Notícias, 2019)
Amblyomma oblongoguttatum is a tick that is a parasite of mammals and its preferred hosts are the wild pigs, tapirs and small rodents, being collected also parasitizing domestic dogs and eventually humans. An Amblyomma oblongoguttatum larva with morphological abnormality was collected along with other specimens (larvae and females) of this species and with morphologically normal Amblyomma naponense nymphs in a wild pig - Pecari tacaju - in a rural area of the state of Rondônia / Brazil, during research of tick-borne disease environments. The morphologically abnormal specimen showed a bifurcation of the posterior region of the opisthosoma, without other altered morphological characters. This is the first record of morphological abnormality at the larval stage of Amblyomma oblongoguttatum.